Splice‐dependent trans‐synaptic PTPδ–IL1RAPL1 interaction regulates synapse formation and non‐REM sleep. (29th April 2020) - Park, Haram; Choi, Yeonsoo; Jung, Hwajin; Kim, Seoyeong; Lee, Suho; Han, Hyemin; Kweon, Hanseul; Kang, Suwon; Sim, Woong Seob; Koopmans, Frank; Yang, Esther; Kim, Hyun; et al.
Abstract: Alternative splicing regulates trans‐synaptic adhesions and synapse development, but supporting in vivo evidence is limited. PTPδ, a receptor tyrosine phosphatase adhering to multiple synaptic adhesion molecules, is associated with various neuropsychiatric disorders; however, its in vivo functions remain unclear. Here, we show that PTPδ is mainly present at excitatory presynaptic sites by endogenous PTPδ tagging. Global PTPδ deletion in mice leads to input‐specific decreases in excitatory synapse development and strength. This involves tyrosine dephosphorylation and synaptic loss of IL1RAPL1, a postsynaptic partner of PTPδ requiring the PTPδ‐meA splice insert for binding. Importantly, PTPδ‐mutant mice lacking the PTPδ‐meA insert, and thus lacking the PTPδ interaction with IL1RAPL1 but not other postsynaptic partners, recapitulate biochemical and synaptic phenotypes of global PTPδ‐mutant mice. Behaviorally, both global and meA‐specific PTPδ‐mutant mice display abnormal sleep behavior and non‐REM rhythms. Therefore, alternative splicing in PTPδ regulates excitatory synapse development and sleep by modulating a specific trans‐synaptic adhesion. Synopsis: Global deletion of PTPδ, a presynaptic adhesion molecule, disrupts excitatory synapse formation and NREM sleep. Deletion of the PTPδ‐meA splice insert, critical for trans‐synaptic IL1RAPL1 binding, recapitulates the synaptic and behavioural changes induced by global PTPδ knockout. Global PTPδ deletion in mice leads to input‐specific decreases in excitatory synapse development and strength. This involves tyrosine dephosphorylation and synaptic loss of IL1RAPL1, a postsynaptic adhesion molecule binding to PTPδ with the meA splice insert. Deletion of the PTPδ‐meA splice insert recapitulates biochemical, synaptic, and behaviour changes induced by global PTPδ knockout. Abstract : Global deletion of PTPδ, a presynaptic adhesion molecule, disrupts excitatory synapse formation and NREM sleep. Deletion of the PTPδ‐meA splice insert, critical for trans‐synaptic IL1RAPL1 binding, recapitulates the synaptic and behavioural changes induced by global PTPδ knockout.